A intimidade era teatro: tensões entre autobiografia e ficção nas poéticas de Ana Cristina Cesar e Sylvia Plath - Caspon, Vanessa [UNIFESP] (2019)
This work aims to analyze the books Ariel (2013), by Sylvia Plath (1932-1963), and A teus pés (2013), by Ana Cristina Cesar (1952-1983), focusing on elements that contribute to the construction of lyrical subjectivity in some of their poems. From the reading of the selected poems, as well as the critical works about them, this work aims to observ a tension between two poetical standings: the pursuit of the reader for coincidences between biographical happenings and the poetic text, for the cry of the heart of the one who writes the verses, and the poetic text while an aesthetic construction of language. In case of Sylvia Plath’s work, we will investigate the tensions between the sentimental flow in poetic verses, such as proposed by her contemporaries at the aesthetic called as confessionalist from the 1950s and the 1960s in the USA and in England; and the intense dialogue with literary and artistic tradition, as well as the keen formal composition of her poems, such as the kaleidoscopic imagery of the secrets, confessions, bodies. In Ana Cristina Cesar’s, we will analyze the tension between the manifestation of the poem called spontaneous of the named “poesia marginal” of the Brazilian 1970s, as well as the poetic strategy of inviting her reader to an intimate moment and her consequential rupture for poetic creationg, the dialogue with the artistic and literary traditions, the deviation of intimacy by the own poetic structure. For the analysis, we selected four poems: “A Secret” and “Daddy”, by Sylvia Plath; and “Atrás dos olhos das meninas sérias” and “Sete chaves”, by Ana Cristina Cesar. It is used as critical works such as Carl Rollyson’s (2015) and Susan Van Dyne’s (2006), concerning historical background of Sylvia Plath’s work; also, Italo Moriconi’s (1996) and Marcos Siscar’s (2006) texts on reception and literary production of Ana Cristina Cesar.